2009
DOI: 10.1258/om.2009.090030
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial haemorrhage in pregnancy

Abstract: Summary: Intracranial haemorrhage (ICH) is a rare, yet potentially devastating event in pregnancy. There is a risk of maternal mortality or morbidity and a significant risk to the unborn child. The risk of haemorrhage increases during the third trimester and is greatest during parturition and the puerperium. ICH can be extradural, subdural, subarachnoid or intraparenchymal. Causes of bleeding include trauma, arteriovenous malformations, aneurysms, preeclampsia/eclampsia and venous thrombosis. Urgent neurosurgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 58 publications
2
29
0
2
Order By: Relevance
“…Several studies have reported vascular anomalies as the most common etiology of ICH in pregnancy. 1,5 Although the changed hemodynamics of pregnancy, including increased blood volume and venous blood pressure, suggest increased risk of aneurysmal rupture or AVM bleeding, the literature is divided on whether this theoretical risk manifests clinically. 2,4 Cavernous malformations may enlarge, but are not a high-flow system (unlike AVMs), and have not shown increased risk of bleeding.…”
Section: Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported vascular anomalies as the most common etiology of ICH in pregnancy. 1,5 Although the changed hemodynamics of pregnancy, including increased blood volume and venous blood pressure, suggest increased risk of aneurysmal rupture or AVM bleeding, the literature is divided on whether this theoretical risk manifests clinically. 2,4 Cavernous malformations may enlarge, but are not a high-flow system (unlike AVMs), and have not shown increased risk of bleeding.…”
Section: Sectionmentioning
confidence: 99%
“…2,4 Cavernous malformations may enlarge, but are not a high-flow system (unlike AVMs), and have not shown increased risk of bleeding. 5 Ischemic stroke etiologies include those common in the nonpregnant population: cardioembolic, artery-to-artery thromboembolism, arterial dissection, and hypercoagulable disorders. 4 Preeclampsia and eclampsia are important risk factors for both ischemic and hemorrhagic stroke.…”
Section: Sectionmentioning
confidence: 99%
“…Ча-стота ОНМК в III триместре, в родах и в послеродо-вом периоде, по данным литературы [11], увеличива-ется. По данным нашего исследования [12], в 64,7% случаев ОНМК развивалось в III триместре, в родах и в послеродовом периоде.…”
Section: материал и методыunclassified
“…2 Changes in vascular physiology and blood volume during pregnancy may account for the increased risk of hemorrhage. 3 Blood volume increases by 50% during pregnancy and reaches a plateau at 32 weeks gestation. 3 Accordingly, cardiac output increases by 50% during the first stage of labor compared with prepregnancy baseline, although the effects of this transient but substantial increase on ICH risk are unknown.…”
mentioning
confidence: 99%
“…3 Blood volume increases by 50% during pregnancy and reaches a plateau at 32 weeks gestation. 3 Accordingly, cardiac output increases by 50% during the first stage of labor compared with prepregnancy baseline, although the effects of this transient but substantial increase on ICH risk are unknown. 4 In a retrospective analysis of 50,700 admissions for delivery, intracranial hemorrhage was identified as the cause of 13 of the 34 identified strokes.…”
mentioning
confidence: 99%